Unmet Needs and Coping Strategies of Older Underserved Veterans During the COVID-19 Pandemic - Trenton M. Haltom; Joyce Tiong; Tracy L. Evans; Nipa Kamdar; Gala True; Mark E. Kunik (SAGE Publishing, 2023)
Introduction: The COVID-19 pandemic has had profound impacts on people with diabetes, a group with high morbidity and mortality. Factors like race, age, income, Veteran-status, and limited or interrupted resources early in the COVID-19 pandemic compounded risks for negative health outcomes. Our objective was to characterize the experiences and needs of under-resourced Veterans with type 2 diabetes during the COVID-19 pandemic. Methods: We conducted semi-structured qualitative interviews (March through September 2021) with U.S. military Veterans with diabetes. Transcripts were analyzed using a team-based, iterative process of summarizing and coding to identify key themes. Participants included Veterans (n = 25) who were mostly men (84%), Black or African American (76%), older (mean age = 62.6), and low-income (<$20 000/year; 56%). Most participants self-reported moderate (36%) or severe (56%) diabetes-related distress. Results: Shutdowns and social distancing negatively impacted Veterans' social, mental, and physical health. Veterans reported feeling increased isolation, depression, stress, and unmet mental health needs. Their physical health was also negatively affected. Despite pandemic-related challenges, Veterans adapted with new technological skills, appreciating their families, staying active, and relying on their religious faith. Conclusions: Veterans' experiences during the pandemic revealed the importance of social support and access to technology. For those without social support, peer support could protect against negative health outcomes. Emergency-preparedness efforts for vulnerable patients with type 2 diabetes should include raising awareness about and increasing access to technological resources (eg, Zoom or telehealth platforms). Findings from this study will help tailor support programs for specific populations' needs in future health crises.